PERAN AKUNTANSI SYARIAH DALAM MENINGKATKAN KINERJA KEUANGAN DAN KEPATUHAN TERHADAP PRINSIP ISLAM 089669130070 - Rina; Fadly Yashari Soumena (LPPM STAI Muhammadiyah Probolinggo, 2025)
Sharia accounting is an accounting system that operates according to Islamic law principles, integrating ethical and moral values in financial transactions. This study uses a qualitative method with a descriptive approach to explain the role of sharia accounting in improving the finances of Islamic financial institutions. The findings show that transparency and accountability are the main pillars, increasing stakeholder trust and reducing the risk of non-compliance. In addition, sharia-based financial planning helps institutions avoid prohibited practices such as usury, while encouraging investment in productive sectors. Sharia supervision and audits ensure compliance with Islamic principles, enhancing the integrity and reputation of the institution. Thus, sharia accounting not only functions as a performance measurement tool, but also strengthens the legitimacy of the institution in the eyes of the public.